The Reciprocal Interaction Between LncRNA CCAT1 and miR-375-3p Contribute to the Downregulation of IRF5 Gene Expression by Solasonine in HepG2 Human Hepatocellular Carcinoma Cells - Liu, Zheng; Ma, ChangJu; Tang, XiaoJuan; Tang, Qing; Lou, LiJie; Yu, Yaya; Zheng, Fang; Wu, JingJing; Yang, Xiao-bo; Wang, Wei; Hann, Swei Sunny (Frontiers in Oncology, 2019)
Solasonine (SS), a natural glycoalkaloid component, has been shown potent inhibitory activity and cytotoxicity against many cancer types. However, the precise mechanisms underlying this, particularly in hepatocellular carcinoma (HCC) are poorly understood. In this study, we showed that SS inhibited growth of HCC cells. Mechanistically, we observed that SS increased the expression of miR-375-3p whereas reducing levels of long non-coding RNAs (lncRNAs) CCAT1 was noticed in HepG2 HCC and other cells. In addition, we found that SS repressed transcription factors SP1 and interferon regulatory factor 5 (IRF5) protein expressions. There was a reciprocal interaction among miR-375-3p, CCAT1 and SP1. Moreover, SS inhibited IRF5 promoter activity, which was not observed in cells transfected with excessive expressed SP1 vectors. Interestingly, exogenously expressed IRF5 showed to reverse SS-inhibited CCAT1 and induced-miR-375-3p expressions; and neutralized SS-inhibited growth of HCC cells. Similar results were also found in vivo mouse model. Collectively, our result show that SS inhibits HepG2 HCC growth through the reciprocal regulation between the miR-375-3p and lncRNA CCAT1, this result in transcription factor SP1-mediated reduction of IRF5 expression. The regulations and interactions among miR-375-3p, CCAT1, SP1 and IRF5 axis unveil a novel molecular mechanism underlying the anti-HCC growth by SS. IRF5 may be a potential target for treatment of HCC.